THE EFFECTIVENESS OF THE APPLICATION FOR REPORTING THE ARRIVAL AND DEPARTURE OF SHIPS (SIKAPAL) AT THE CLASS I IMMIGRATION OFFICE OF TPI BENGKULU - Mila Rosmaya; W Wilonotomo; Rizki Cahyosha (Polteknik Imigrasi, 2021)
Indonesia as a country that has many seaports makes immigration checkpoints used as traffic in and out of foreigners. As a result, the intensity of incoming and outgoing foreign ships becomes large. Bengkulu Immigration Office creates an innovative immigration service that facilitates the process of checking foreign ships. The arrival and departure reporting application (sikapal) was created to increase the productivity of the performance of immigration officers and ship agents in the process of submitting arrival and departure data for foreign ships at immigration checkpoints. This study aims to determine the effectiveness of using sikapal application in facilitating the work of immigration officers and the constraints on effectiveness in implementing the sikapal application. The type of method used is qualitative-descriptive, data collection techniques obtained from observations, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. The results of this study indicate that the sikapal application has so far been effective. This is based on the focus of research that uses indicators of effectiveness according to Sutrisno where the measurements include understanding the program, being on target, on time, achieving goals, and real changes. The obstacles in its implementation have not yet obtained the MRZ (Machine Readable Zone) scan permission, unstable network conditions, and the unavailability of the Website and IOS versions of the application.